Emerging market hedge funds: Analysis of security selection and market timing - Dutta, S. (Banking and Finance Review, 2012)
Recent studies have documented that it is only very recently that the Emerging Market Hedge Funds (EMHFs) have started mimicking the performance pattern of regular Hedge Funds. These findings therefore motivate us to analyze the market timing and security selection skills of EMHF managers. Rolling regression technique is employed to analyze the above mentioned issues on a time-varying dimension. The rolling market timing regression results suggest that the EMHF managers do not exhibit consistently superior security selection or market timing skills even in an up-market scenario. The static market timing models however, indicate significant outperformance due to superior security selection and significant underperformance due to perverse market timing for the EMHFs in general. Multifactor asset class regressions, using fund-level data, reaffirm the notion that the EMHFs mimic the performance pattern reported for mutual funds in the mutual fund literature. © 2012, Banking and Finance Review.
Keywords: Emerging market; Hedge Funds; Security selection; dept.fin; ⛔ No DOI found